Interactive Educational Game Media in Metacognitive Learning to Improve Conceptual Understanding and Science Literacy In Grade V IPA Content in Elementary School - I Putu Angga Suryadi; I Wayan Widiana; Gede Wira Bayu (Jurnal Media dan Teknologi Pendidikan, 2025)
The problem addressed in this study is the low level of conceptual understanding and scientific literacy among students. To address this issue, the study aims to develop an interactive educational game media based on metacognitive learning to improve the conceptual understanding and scientific literacy of fifth-grade elementary school students. This development research employs the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. The study involved 32 fifth-grade students and a homeroom teacher as research subjects. Data collection techniques included questionnaires and tests, with instruments designed based on a rating scale guideline. Data were analyzed using Aiken’s V formula to assess validity, percentage formulas to measure practicality, and paired t-tests to evaluate effectiveness. The results show that the developed media has a very high level of validity (0.98), an excellent level of practicality (98.02%), and is proven effective in enhancing students' conceptual understanding and scientific literacy. Therefore, it can be concluded that the metacognitive-based interactive educational game media developed in this study is valid, practical, and effective in improving fifth-grade students’ conceptual understanding and scientific literacy. Moreover, this media serves as an innovative, engaging, and adaptive alternative strategy for IPAS (Science and Social Education) learning that aligns with students’ needs and learning characteristics in the digital era.